Meta-analysis of prognostic factors for patients with colorectal peritoneal metastasis undergoing cytoreductive surgery and heated intraperitoneal chemotherapy. Issue 5 (27th June 2019) - Hallam, S; Tyler, R; Price, M; Beggs, A; Youssef, H
Abstract: Background: Up to 15 per cent of colorectal cancers present with peritoneal metastases (CPM). Cytoreductive surgery and heated intraperitoneal chemotherapy (CRS + HIPEC) aims to achieve macroscopic tumour resection combined with HIPEC to destroy microscopic disease. CRS + HIPEC is a major operation with significant morbidity and effects on quality of life (QoL). Improving patient selection is crucial to maximize patient outcomes while minimizing morbidity and mortality. The aim of this study was to identify prognostic factors for patients with CPM undergoing CRS + HIPEC. Methods: A systematic search of MEDLINE, Embase and Cochrane Library electronic databases was performed using terms for colorectal cancer, peritoneal metastasis and CRS + HIPEC. Included studies focused on the impact of prognostic factors on overall survival following CRS + HIPEC in patients with CPM. Results: Twenty-four studies described 3128 patients. Obstruction or perforation of the primary tumour (hazard ratio (HR) 2·91, 95 per cent c.i. 1·5 to 5·65), extent of peritoneal metastasis as described by the Peritoneal Carcinomatosis Index (PCI) (per increase of 1 PCI point: HR 1·07, 1·02 to 1·12) and the completeness of cytoreduction (CC score above zero: HR 1·75, 1·18 to 2·59) were associated with reduced overall survival after CRS + HIPEC. Conclusion: Primary tumour obstruction or perforation, PCI score and CC score are valuable prognostic factors in the selection of patients with CPM for CRS + HIPEC. Graphical Abstract: Cytoreductive surgery and heated intraperitoneal chemotherapy (CRS + HIPEC) for colorectal peritoneal metastasis (CPM) aims to achieve macroscopic tumour resection combined with HIPEC to destroy microscopic disease. The 5-year overall survival rate ranges from 20 to 65 per cent in selected patients. CRS + HIPEC is, however, a major operation with significant morbidity and effects on quality of life, and patient selection is crucial. This systematic review aimed to identify prognostic factors for patients with CPM undergoing CRS + HIPEC. ECOG, Eastern Cooperative Oncology Group; PM, peritoneal metastasis; GI, gastrointestinal; PCI, Peritoneal Carcinomatosis Index; CC, completeness of cytoreduction. Both tumour and surgical factors play a role